Recuperação de pastagens de Brachiaria decumbensdegradada com introdução de Stylosanthes e adubação fosfatada1 - Fabrice, Carlos Eduardo Santos; Soares Filho, Cecílio Viega; Pinto, Marcos Franke; Perri, Sílvia Helena Venturoli; Cecato, Ulysses; Mateus, Gustavo Pavan (UFBA - Universidade Federal da Bahia, 2015)
SUMMARY This work aimed at evaluating the possibility of recovery of a degradedBrachiaria decumbens pasture with the introduction ofStylosanthes legumes and phosphorus fertilization. The experiment consisted of different input methods in a randomized complete block design with split plots (fertilized with and without phosphorus), with four repetitions and composed by the following treatments: control Brachiaria decumbens; partial drying with 1.5L ha-1 glyphosate; total drying with 3.0L ha-1 glyphosate; tillage; scarifying the soil; rome harrowing and plowing more harrowing. In the rome harrowing and plowing more harrowing treatments , the legume sowing was made by throwing, and the others by direct seeding. Six cuts were made to separate the morphological components of fodder and botanical composition. The highest total dry mass accumulation was found for partial drying with 1.5 L ha-1 glyphosate, rome harrowing, plowing more harrowing and total drying with 3.0 L ha-1 glyphosate in relation to tillage and control groups. The chemical composition was better in the springtime, CP and ADF showed significant differences between all treatments (P<0.05). The phosphate fertilizer took effect to ADF in the spring and fall seasons. The introduction of legumes through harrowing and plowing more harrowing, promoted the highest productivity in the total biomass and the partial and total drying increased the legume participation. The phosphorus fertilization only showed positive results in productivity and legume participation during the summer season.

RESUMO Objetivou-se avaliar a possibilidade de recuperação deumapastagem degradada, deBrachiaria decumbens, com a introdução da leguminosaStylosanthes e adubação fosfatada. O experimento constou de distintos métodos de introdução em um delineamento experimental em blocos casualizados com parcelas subdivididas (adubado com e sem fósforo), com quatro repetições e compostos pelos tratamentos: testemunha Brachiaria decumbens; dessecação parcial com 1,5L ha-1 de glifosato; dessecação total com 3,0L ha-1 de glifosato; plantio direto; escarificação do solo; gradagem rome e aração mais gradagem. Nos tratamentos gradagem rome e aração mais gradagem a semeadura da leguminosa foi feita a lanço e os demais na forma de semeadura direta. Foram realizados seis cortes para separação dos componentes morfológicos da forragem e composição botânica. Os maiores acúmulos de massa seca total foram encontrados para dessecação parcial com 1,5L ha-1 de glifosato, gradagem rome, aração mais gradagem e dessecação total com 3,0L ha-1 de glifosato em relação aos tratamentos plantio direto da leguminosa e testemunha. A composição bromatológica foi melhor na estação da primavera, PB e FDA apresentaram diferenças significativas entre todos os tratamentos (P<0,05). O adubo fosfatado teve efeito para FDA nas estações da primavera e outono. A introdução da leguminosa, por meio de gradageme aração + gradagem,promoveu a maior produtividade na biomassa total e a dessecação parcial e totalaumentaram a participação da leguminosa. A adubação fosfatada somente apresentou resultados positivos na produtividade e participação da leguminosa durante a época de verão.
Recovery of degraded “Brachiaria decumbens” pasture with the introduction of Stylosanthes and phosphorus fertilization
Keywords: cultivation; degradation; fertilizer; pasture; tillage; adubo; consorciação; degradação; pasto; plantio direto